Evidence from Business Strategy of Mutual Fund Managers after the Financial Crisis - Panel Smooth Transition Regression Model - Lee, Joe-Ming (Journal of Asian Business Strategy, 2013)
This study applies by the panel transition regression (PSTR) model to investigate the nonlinear dynamic relationship between equity fund flow and investment volatility in Taiwan. Our empirical results show that the equity fund managers will be different business strategy under the volatility threshold value and the control variables of asset of funds, management fee and Turnover indicator. After the financial crisis, the threshold of volatility will be an important index to different business strategy of equity fund managers. Belong to low-risk equity funds, the equity fund managers tend to attract investors to increase fund performance, efforts to expand the fund size, and the better the performance of the fund, but charge lower management fee, increased investors purchase fund incentives, as well as reduce the turnover rate, the pursuit of fund performance. Conversely, belong to high-risk equity funds, the equity fund managers to increase fund performance, efforts to expand the fund size, and the better the fund performance of the funds charge higher management fees, increased operating income, and the use of the high turnover rate, the pursuit of fund performance. Finally, the equity fund managers in order to restore investor confidence, for different risk bearing capacity of the investors, the use of different business strategies to meet the investment demands of investors, as well as trying to make a loss of investors to reflux, and efforts to reach stable company revenue goals.